Sustainable Energy and Transportation Technologies and Policy (Energy, Environment, and Sustainability,, 2018)
This book presents an integrated approach to sustainably fulfilling energy requirements, considering various energy-usage sectors and applicable technologies in those sectors. It discusses smart cities, focusing on the design of urban transport systems and sources of energy for mobility. It also shares thoughts on individual consumption for ensuring the sustainability of energy resources and technologies for emission reductions for both mobility and stationary applications. For the latter, it examines case studies related to energy consumption in the manufacturing sector as well as domestic energy requirements. In addition it explores various distribution and policy aspects related to the power sector and sources of energy such as coal and biomass. This book will serve as a valuable resource for researchers, practitioners, and policymakers alike. .